2008
DOI: 10.1002/jbm.a.31899
|View full text |Cite|
|
Sign up to set email alerts
|

Increased chondrocyte adhesion on nanotubular anodized titanium

Abstract: Previous studies have demonstrated increased osteoblast (bone-forming cells) functions (including adhesion, synthesis of intracellular collagen, alkaline phosphatase activity, and deposition of calcium-containing minerals) on titanium anodized to possess nanometer features compared with their unanodized counterparts. Such titanium materials were anodized to possess novel nanotubes also capable of drug delivery. Since titanium has not only experienced wide spread commercial use in orthopedic but also in cartila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 24 publications
2
35
0
1
Order By: Relevance
“…In addition, previous research has clearly proven that nanotube surfaces promote bone, skin, and other tissue growth more than current conventional surfaces. 16,[20][21][22] Several papers have been published that have focused on the applications of titanium nanotube drug coatings, but none of them has examined the use of this delivery system at the percutaneous site. 18,23,24,35 Titanium …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, previous research has clearly proven that nanotube surfaces promote bone, skin, and other tissue growth more than current conventional surfaces. 16,[20][21][22] Several papers have been published that have focused on the applications of titanium nanotube drug coatings, but none of them has examined the use of this delivery system at the percutaneous site. 18,23,24,35 Titanium …”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown better cell attachment to nanotubular surfaces that are more hydrophobic than unmodified surfaces. 20,41,42 But according to some results in the literature, fibroblasts prefer a smooth surface to a rough surface. 43 To prevent any side effect of CNN2 in the bone healing process, a two-stage solution may be a good choice for the further clinic application of the CNN2-loaded titania nanotube surface on percutaneous implant.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Diameters of 15-20 nm are optimal and in case of such TNT presence on the surface of titanium implants, increase in adhesion and proliferation of several types of living cells, such as fibroblasts, osteoblasts, osteoclasts, mesenchymal stem cells, hematopoietic stem cells, and endothelial cells, was confirmed [127][128][129][130][131][132][133][134]. Higher tube diameters (>100 nm) have no positive influence on the increasing of adhesion or proliferation and some authors have shown that TNT of such diameters led to apoptosis, i.e., programmed cell death [135].…”
Section: Titania Nanotubes (Tnts)mentioning
confidence: 91%
“…In order to obtain the best performance during clinical use, mechanical properties of implants need to be investigated and understood. To date, the growth of cell cultures has been used to study implants [6][7][8][9][10][11][12][13][14], but few studies have investigated the mechanical properties of nanotextured implants [15]. Titanium orthopedics have many advantages over traditional stainless steel implants, such as: better osteo-integration, a modulus of elasticity closer to that of bone, higher strength, and lower cost [12].…”
Section: Introductionmentioning
confidence: 99%